Giant Scrotal Hydrocele and Bilateral Leg Lymphedema as Clinical Manifestation of Chronic Lymphatic Filariasis - Indra Wijaya; Winfrey Pangestu (Interna Publishing, 2016)
A 51-year-old male came with the complaint of recurrent swelling in the scrotum and legs. Swelling of the scrotum first appeared 17 years ago in the left scrotum approximately the same size as an apple and underwent surgery. However, 2 years after surgery, the swelling reemerged and gradually increase in size in both scrotums. Left leg swelling began to emerge 5 years ago followed by right leg 3 years after. The patient lives in Sarmi regency Papua province (endemic).